2008
DOI: 10.1021/jp8012305
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Charge-Transfer-to-Solvent Band in the Absorption Spectra of Hydrogen Halides on Ice Nanoparticles: Spectroscopic Evidence for Acidic Dissociation

Abstract: Extensive ab initio calculations complemented by a photodissociation experiment at 193 nm elucidate the nature of hydrogen halide molecules bound on free ice nanoparticles. Electronic absorption spectra of small water clusters (up to 5 water molecules) and water clusters doped with hydrogen fluoride, hydrogen chloride and hydrogen bromide were calculated. The spectra were modeled at the time-dependent density functional (TDDFT) level of theory with the BHandHLYP functional using the reflection principle. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…[8][9][10][11][12][13][14] When this experiment was moved to our laboratory in Prague, the studies have been extended to other systems, e.g., hydrogen halides on ice nanoparticles [15][16][17] or clusters of biologically relevant molecules. For instance, photodissociation of hydrogen halides on/in various large rare gas clusters HX·Rg n (n ∼ 10 2 atoms) was studied on a versatile cluster beam apparatus in Göttingen.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] When this experiment was moved to our laboratory in Prague, the studies have been extended to other systems, e.g., hydrogen halides on ice nanoparticles [15][16][17] or clusters of biologically relevant molecules. For instance, photodissociation of hydrogen halides on/in various large rare gas clusters HX·Rg n (n ∼ 10 2 atoms) was studied on a versatile cluster beam apparatus in Göttingen.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2C shows that the HCl molecules on the water cluster do not coagulate to HCl clusters as opposed to the Ar case shown in Figure 2A. An example of the H-fragment KED measured in several our studies (Poterya et al, 2007, 2008a; 2011; Ončák et al, 2008, 2011) is shown in Figure 2D. It exhibits some differences compared to the rare gas case: the direct exit fast fragments are missing entirely as well as the sharp peak at zero kinetic energy (cage effect); rather slow fragments extending to ≈0.5 eV occur with a broad maximum below 0.1 eV.…”
Section: Resultsmentioning
confidence: 62%
“…Ončák et al (2008, 2011) and Poterya et al, (2011) argued that the acidic dissociation in the ground state leads to a significant red-shift of the absorption spectra of the X − H 3 O + (H 2 O) n −1 species with possible atmospheric consequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations